Debit Card and Credit Card Fraud Investigation in Bengaluru City - Mr. Yerriswamy K, Dr. G. S. Venumadhava (Mathematical Statistician and Engineering Applications, 2022)
Debit card and Credit card fraud is a type of identity theft that involves the unlawful use of another person’s credit card information in order to charge transactions to the account or withdraw funds from it. Debit card fraud happens when a criminal obtains one debit card number (and, in some situations, their personal identification number (PIN)) in order to make unauthorized purchases or withdraw cash from their account. The current study has used secondary data which included 300 Police reported cases of debit/credit card frauds that have been reported in Bengaluru City over the past five years. The collected data have been organized and looked into thoroughly for the details pertain to the crime. The were analysed and interpreted using statistics to find the trends and causes for these crimes. The study has employed both descriptive (frequency and percentage) and inferential statistics (chi-square test) using SPSS for windows. The obtained results were quantitatively interpreted and further qualitatively interpreted with supporting literature.The results revealedthe number of Police reported cases related to Debit card frauds was higher than Credit card frauds and this might be due to the excessive use of debit cards. Males were the frequent victims of financial fraud as women tend to stay away from risks and are slightly careful about their privacy and identity. The Eastern part of Bangalore which is the Information Technology hub (IT hub) of the city was found to have reported the majority of financial fraud cases. Nowadays OTP frauds have become common because of the effortless way to do it. Individuals with private jobs are more prone to financial fraud than students as having a decent salary that is being saved in their accounts is a guarantee for the fraudster. It was found that criminals focused on making quick money with small amounts rather than aiming for larger ones to be safe from being caught or penalized.